APLIKASI METODE INDUCED POLARIZATION (IP) UNTUK MENGIDENTIFIKASI PENYEBARAN MINERAL LOGAM DI DAERAH LEON - Nugraheni, Elleona Septi; Yatini, Y; Santoso, Agus (Indonesian Mining Journal, 2023)
The research was conducted in the Leon area to determine the presence and quantity of metallic mineral resources. The stratigraphy of the study area is composed of alluvium and coastal deposits, Molasa Sarasin Formation, Tinombo Formation, and Intrusion. Exploration was carried out in the Leon area using Induced Polarization Method with a dipole-dipole configuration with an area of ​​950 m2. The length of the track is 580 meters with a North-South orientation. The number of tracks in this study was 15, with spacing electrodes as far as 20 meters and n = 1-10. The analysis showed that the distribution of resistivity values ​​in the study area was from (13.6 to 1337) Ωm, while the chargeability values ​​had a range of values ​​(1.7 to 50.6) ms. The low resistivity values ​​below 50 Ωm are interpreted as claystone to sandstone and the medium resistivity values ​​between 50 Ωm - 500 Ωm are interpreted as compact sandstone to breccia. The resistivity values ​​above 500 Ωm are interpreted as igneous rock. The presence of metallic minerals in the study area is characterized by changeability values ​​above 22 ms in claystone, sandstone, breccia, and igneous rock. Calculating hypothetical resources was conducted the Block model method at Oasis Montaj that obtained 11.8 million tons of resources.